CLINICAL AND IMAGING CHARACTERISTICS OF POST-TRAUMATIC ORBITAL DEFORMITIES AT 108 MILITARY CENTRAL HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the clinical and imaging characteristics of post-traumatic orbital deformities at Military Central Hospital 108 from September 2018 to August 2019.Methods: A descriptive cross-sectional study with analysis, combining retrospective and prospective data. Patients had a history of maxillofacial trauma more than 6 months earlier and were diagnosed with post-traumatic orbital deformities.Results: Among the 35 study patients, the mean age was 30 years, with the youngest aged 17 years and the oldest aged 50 years. The male-to-female ratio was 2.5:1. The main cause of trauma was traffic accidents (91.4%). The most common subjective symptoms were diplopia (42.9%) and blurred vision (31.4%); the most common physical sign was enophthalmos (85.7%); the most common associated injury was maxillofacial fracture (91.4%). The most common sites of bony deformity on computed tomography were the inferior orbital rim (82.9%) and the orbital floor (85.7%). Computed tomography detected more lesions than conventional radiography (p < 0.05).Conclusion: The most common manifestations of post-traumatic orbital deformities were diplopia, blurred vision, and enophthalmos. The most common bony deformity involved the inferior orbital rim. Computed tomography provided clearer images and detected more lesions than conventional radiography.
Keywords: post-traumatic orbital deformities, clinical characteristics, imaging characteristics